ELEVATING JUSTICE: A SCRUTINY OF INVESTIGATION WARRANT SUBMISSIONS ALIGNED WITH VALUE PRINCIPLES - Hidayat, Aulia Rahman; Wibowo, Agung Santoso (Top Journal of Public Policy and Administration (TJPPA), 2024)
The criminal justice system is fundamentally grounded in the presumption of innocence until guilt is proven, underscoring the importance of safeguarding the rights of individuals involved (Baker & Williams, 2018). This necessitates a vigilant examination of the legal framework governing investigation warrant submissions, ensuring alignment with justice value principles. Investigation warrants, authorizing actions such as property searches, evidence seizures, and suspect arrests, play a pivotal role in law enforcement procedures (Gosselin & Bouchard, 2019). Nevertheless, the process of acquiring these warrants must adhere to standards of lawfulness, fairness, and justice. The essence of justice value lies in upholding principles of fairness, equity, and impartiality within the criminal justice system (Tyler, 2018). This concept acts as a cornerstone, guaranteeing equitable treatment and the protection of individual rights. It serves as a crucial factor in cultivating public trust in the criminal justice system, ensuring that law enforcement agencies steer clear of discriminatory practices (Schedler, 2020). Empirical evidence underscores the tight link between public trust and the perception of fairness and impartiality within the criminal justice system (Sunshine & Tyler, 2003). Notably, research indicates that individuals perceiving the system as unfair are less likely to cooperate with law enforcement and exhibit a higher likelihood of engaging in illegal activities (Gau & Brunson, 2010). This study delves into the intricate relationship between justice value principles, the process of obtaining investigation warrants, and their broader implications on public trust and cooperation with law enforcement. By examining the nexus between procedural fairness in the legal system and societal attitudes, this research aims to contribute to the ongoing discourse on the importance of aligning investigative practices with justice value principles. Insights gleaned from this study have the potential to inform policy discussions, guiding the refinement of legal frameworks to ensure a more just, equitable, and trustworthy criminal justice system.